Grain Enlargement and Defect Passivation with Melamine Additives for High Efficiency and Stable CsPbBr3 Perovskite Solar Cells. Issue 7 (5th March 2020) - Zhu, Jingwei; He, Benlin; Gong, Zekun; Ding, Yang; Zhang, Wenyu; Li, Xueke; Zong, Zhihao; Chen, Haiyan; Tang, Qunwei
Abstract: The preparation of high‐quality perovskite films with low grain boundaries and defect states is a prerequisite for achieving high‐efficiency perovskite solar cells (PSCs) with good environmental stability. An effective additive engineering strategy has been developed for simultaneous defect passivation and crystal growth of CsPbBr3 perovskite films by introducing 1, 3, 5‐triazine‐2, 4, 6‐triamine (melamine) into the PbBr2 precursor solution. The resultant melamine–PbBr2 film has a loose, large‐grained structure and decreased crystallinity, which has a positive effect on the crystallization process of the perovskite as it retards the crystallization rate as a result of the interaction between melamine and lead ions. Additionally, the passivation by melamine gives a high‐quality CsPbBr3 perovskite film with fewer grain boundaries, lower defect densities, and better energy level matching is achieved by multistep liquid‐phase spin‐coating, which greatly suppresses the nonradiative recombination resulting from the defects and promotes charge extraction at the interface. A champion power conversion efficiency as high as 9.65 % with a promising open‐circuit voltage of 1.584 V is achieved for PSCs with an architecture of fluorine‐doped tin oxide/c‐TiO2 / m ‐TiO2 /melamine‐added CsPbBr3 /carbon‐based hole‐transporting layer. Furthermore, the unencapsulated melamine‐added CsPbBr3 PSC shows superior thermal and humidity stability in ambient air at 85 °C or 85 % relative humidity over 720 h. Abstract : Against the grain : Adding melamine maximizes grain size and minimizes defects in CsPbBr3 perovskite films. The resulting CsPbBr3 perovskite solar cell (PSC) free of encapsulation achieves a champion power conversion efficiency (PCE) of 9.65 % and excellent thermal and humidity stability.